Genotype and residual enzyme activity in medium‐chain acyl‐CoA dehydrogenase (MCAD) deficiency: Are predictions possible?. Issue 4 (25th February 2021) - Tucci, Sara; Wagner, Christine; Grünert, Sarah C.; Matysiak, Uta; Weinhold, Natalie; Klein, Jeannette; Porta, Francesco; Spada, Marco; Bordugo, Andrea; Rodella, Giulia; Furlan, Francesca; Sajeva, Anna; et al.
Abstract: Medium‐chain acyl‐CoA dehydrogenase deficiency (MCADD) is the most common defect of mitochondrial β‐oxidation. Confirmation diagnostics after newborn screening (NBS) can be performed either by enzyme testing and/or by sequencing of the ACADM gene. Here, we report the results from enzyme testing in lymphocytes with gene variants from molecular analysis of the ACADM gene and with the initial acylcarnitine concentrations in the NBS sample. From April 2013 to August 2019, in 388 individuals with characteristic acylcarnitine profiles suggestive of MCADD the octanoyl‐CoA‐oxidation was measured in lymphocytes. In those individuals with residual activities <50%, molecular genetic analysis of the ACADM gene was performed. In 50% of the samples (195/388), MCADD with a residual activity ranging from 0% to 30% was confirmed. Forty‐five percent of the samples (172/388) showed a residual activity >35% excluding MCADD. In the remaining 21 individuals, MCAD residual activity ranged from 30% to 35%. The latter group comprised both heterozygous carriers and individuals carrying two gene variants on different alleles. Twenty new variants could be identified and functionally classified based on their effect on enzyme function. C6 and C8 acylcarnitine species in NBS correlated with MCAD activity and disease severity. MCADD was only confirmed in half of the cases referred suggesting a higher false positive rate than expected. Measurement of the enzyme function in lymphocytes allowed fast confirmation diagnostics and clear determination of the pathogenicity of new gene variants. There is a clear correlation between genotype and enzyme function underlining the reproducibility of the functional measurement in vitro.